Efektivitas Latihan Partner Resisted Starts dan Partner Tubing Acceleration Drill dalam Meningkatkan Performa Akselerasi Atlet Sepak Bola Putri - Prayoga, Abah Sandi; Yudistira, Indra; Effendi, Pamungkas Yulian (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2025)
This study aims to analyze the effect of Partner Resisted Starts (PRS) and Partner Tubing Acceleration Drill (PTAD) training on improving sprint speed in female athletes of UNCEN PAPUA FC in 2025. The study used a two-group pre-test and post-test experimental design with a total of 18 athletes divided into two treatment groups. The training program was conducted over six weeks with a frequency of three times per week. Speed data was obtained through a 30-meter sprint test, and data analysis was performed using a paired sample t-test with a significance level of 0.05. The results showed that both training methods had a significant effect on sprint speed improvement (p < 0.001), with a very large effect size (Cohen's d = 1.97 for PRS and 2.48 for PTAD). In general, PRS training was more effective in improving the initial acceleration phase (0–20 meters), while PTAD contributed more to the continued acceleration phase and peak speed (20–30 meters). These findings support the force–velocity relationship theory, which explains that an increase in horizontal force through resistance can accelerate acceleration time. This resistive training also has the potential to improve neuromuscular coordination and joint stability, which are relevant in the context of injury prevention. Therefore, both methods are recommended as effective, affordable, and safe alternatives for speed training in female soccer athletes. Both methods can be applied as efficient and contextual alternatives to speed training in training environments with limited resources